RELIGIOUS THEME IN O' HENRY'S SHORT STORIES: A SOCIOLOGICAL PERSPECTIVE - Cintantya, Putri Beta (2011)
PUTRI BETA CINTANTYA. A 320 070 305. RELIGIOUS THEME IN O' HENRY'S SHORT STORIES: A SOCIOLOGICAL PERSPECTIVE. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. RESEARCH PAPER. 2011. This study examines how religious theme is reflected in O' Henry's short story, based on sociological perspective. The aim of the study is to analyze the short story in terms of its structural elements and based on the Sociological Perspective. This study belongs to qualitative study. In this method, there were two types of data source, which was used, namely primary data and secondary data sources. The primary data source and the object of the study was short stories in The Best of O' Henry by O' Henry, meanwhile the secondary one was any literature related to this study. The writer collected the data from both primary and secondary data sources by taking notes for the texts and selecting the data by rejecting the irrelevant information which did not support the topic of the study. This study used library research to collect the data. The study comes to the following conclusions. First, based on the structural analysis, it is clear that the dominant themes in O' Henry's short stories are religious theme. Second, based on the Sociological analysis, it is evident that there is close relationship between O' Henry's short stories and social reality of American Society at the beginning of twentieth century.